AI Applications in Hellenic Studies. A Survey (Tabanque. Revista Pedagógica, 2024)
This paper brings together the most significant impacts of artificial intelligence (AI) technology in the sphere of Hellenic studies, particularly focusing on areas such as Literature, Palaeography, Epigraphy, Archaeology and Art History. It discusses the emergence of various applications along with the software and methodologies used. The primary aim is to showcase the key advancements in research while also pointing out the limited number of case studies available. AI integration presents numerous opportunities that are gradually being embraced. This comprehensive overview of the current state of affairs aims to demonstrate how our field of expertise can leverage various approaches undertaken, along with their potential for future progress.
Keywords: Artificial Intelligence; AI technology; Hellenic studies; Human Sciences; Digital Humanities; History; Palaeography; Epigraphy; Archaeology; History of Art